5-Years APAP adherence in OSA patients - Do first impressions matter? - van Zeller, M (2013)
Background: Although continuous positive airway pressure (CPAP) is effective in treating obstructive sleep apnoea (OSA), inadequate adherence remains a major cause of treatment failure. This study aimed to determine long term adherence to auto adjusting-CPAP (APAP) and its influencing factors including the role of initial compliance. Methods: Eighty-eight male patients with newly diagnosed moderate/severe OSA were included. After initiation of APAP treatment, patients had periodic follow-up appointments at 2 weeks, 6 months and then annually for at least 5 years. Patient's compliance to therapy was assessed in each appointment and predictors to treatment abandonment and poor compliance were evaluated. Results: The studied population had a mean age of 53.8 years and mean apnoea–hypopnoea index of 52.71/h. The mean time of follow-up was 5.2 (±1.6) years, during that time 22 (25%) patients abandoned APAP, those who maintained treatment had good compliance to it since 94% of them used it more than 4 h/day for at least 70% of days. A significant negative association was found between age, % of days and mean time of APAP use on 12th day and 6th month and the risk of abandoning. APAP use lower than 33% and 57% of days at 12th day and 6th month, respectively had high specificity (∼100%) to detect treatment abandonment. Conclusions: the majority of patients adheres to long term APAP treatment and has good compliance after 5-years of follow-up. Age and initial compliance (% days of use and mean hour/day) have the ability to predict future adherence, as soon as 12 days and 6 months after initiation.